BINA KELUARGA REMAJA (BKR) DALAM RANGKA MENINGKATKAN POLA ASUH REMAJA YANG BENAR DAN TERARAH - Fajar Hidayanto (UII, 2015)
Family the first and top learning place for every teenager. Parenting way will affectthe development of teenager's characters. But, not all parents understand how to dealwith teenager correctly, such as parents at Dusun Jati, Kelurahan Gerbosari, KecamatanSamigaluh, Kabupaten Kulon Progo, Provinsi D.I. Yogyakarta. So, they need an educationabout parenting. Based on these circumstances, the authors organized a